Neutrophil-to-Lymphocyte Ratio and Treatment Failure in Peritoneal Dialysis-Associated Peritonitis - He, Peng; He, Li-jie; Huang, Chen; Hu, Jin-ping; Sun, Shi-ren (Frontiers in Medicine, 2021)
Objective: To explore if there is an association between neutrophil-to-lymphocyte ratio (NLR) and treatment failure in patients with peritoneal dialysis-associated peritonitis (PDAP). Methods: Our cohort involved 337 episodes of PDAP experienced by 202 patients who were undergoing continuous ambulatory peritoneal dialysis at a single center from 1 July 2013 to 30 June 2018. The exposures were log-transformed NLR and a categorical variable grouped by the tertiles of NLR levels (T1, <3.75; T2, 3.75-6.53; and T3, >6.53) at baseline. Generalized estimating equation (GEE) and restricted cubic spline (RCS) analyses were done to determine the association between NLR and treatment failure, defined as catheter removal or all-cause mortality during therapy. Results: After adjusting for confounders, the log-transformed NLR exhibited an incremental relationship with the risk of treatment failure (odds ratio, 1.81; 95% confidence interval, 1.16 to 2.82). RCS analyses showed that the relationship was positively and linearly correlated (P for nonlinearity=0.256). As a 3-level categorical variable, in reference to T1, the T3 of NLR showed a 3.56-fold increased venture of treatment failure in fully adjusted model. Subgroup analyses suggested that the prognostic relevance of NLR in PDAP was particularly significant in nongram-positive peritonitis. Conclusions: A greater level of NLR at baseline was remarkably associated with a higher incidence of treatment failure among PDAP episodes regardless of other potential risk factors.